Contrast-Enhanced Transrectal Ultrasound for Differential Diagnosis of Focal Pathology of Prostate: Single-Center Retrospective Comparative Study - M. Z. Khasanov; M. G. Tukhbatullin; M. N. Nasrullaev (Кубанский научный медицинский вестник)
Background. Prostate cancer is a frequently diagnosed malignant disease in men. At present transrectal ultrasound is the most common technique for imaging the gland. Traditionally, a combination of grayscale and Doppler modes is used. In order to make transrectal ultrasound of the prostate more informative, the contrast-enhanced techniques are recommended to apply. Contrast-enhanced ultrasound can provide quantitative assessment, which, in turn, increases the objectivity of the results obtained.Objective. To evaluate potential of contrast-enhanced transrectal ultrasound for differential diagnosis of focal pathology of the prostate.Methods. A single-center retrospective comparative study of contrast-enhanced transrectal ultrasound of the prostate gland in 66 patients was carried out at the Republican Clinical Oncological Dispansery, the Republic of Tatarstan. The inclusion criteria was the presence of focal pathology in the peripheral zone of the prostate gland. The median age of patients was 67. The following quantitative perfusion parameters were analyzed: time to peak, peak intensity, descending time, area under the curve and an additional index calculated for each of the specified parameters. The resulting enhancement curves were also analyzed by measuring enhancement angles (β) and washout angles (α). SPSS 13.0 (IBM SPSS Statistics, USA) was used for data analysis.Results. The combination of “angle ß ≥69.5°+ angle α≤69.5°” with sensitivity of 92.7%, specificity 80.0% proved to be the most informative. The sensitivity and specificity of the obtained threshold values “enhancement angle ß≥69.5°” comprised 73.2% and 60.0%, respectively, “washout angle α≤69.5°” — 63.4% and 56.0%, respectively. According to the analysis of perfusion quantitative parameters the test “peak intensity ≥ 34.1 dB” with sensitivity of 75.6%, specificity of 84.0% has the most informative value in the diagnosis of prostate cancer.Conclusion. Quantitative analysis of contrast-enhanced transrectal ultrasound of the prostate gland provides objectification of the study, and the use of threshold values increases the informativity in the differential diagnosis of focal lesions of the prostate gland.